Quinolone and indole alkaloids from the fruits of Euodia rutaecarpa and their cytotoxicity against two human cancer cell lines. (January 2015) - Zhao, Nan; Li, Zhan-Lin; Li, Da-Hong; Sun, Ya-Ting; Shan, Dong-Ting; Bai, Jiao; Pei, Yue-Hu; Jing, Yong-Kui; Hua, Hui-Ming
Graphical abstract: Four quinolone alkaloids and three indole alkaloids, along with 30 known ones were isolated from the fruits of Euodia rutaecarpa . Their in vitro cytotoxic activities of these alkaloids against HL-60 and PC-3 cell lines were evaluated. Highlights: 37 alkaloids, including 30 previously known, were isolated from Euodia rutaecarpa . One compound was a hitherto unknown type of indoloquinazoline alkaloid. Cytotoxic activities against HL-60 and PC-3 cell lines were measured in vitro . A preliminary structure–activity relationship was discussed. Abstract: Four quinolone alkaloids (1 –4 ) and three indole alkaloids (20 –22 ), together with 30 known alkaloids (5 –19, 23 –37 ), were isolated from the fruits of Euodia rutaecarpa . Their structures were established by spectroscopic analyses. The in vitro cytotoxic activities of these alkaloids against leukaemia HL-60 and prostate cancer PC-3 cell lines were evaluated.